A compositional model for CO2 flooding including CO2 equilibria between water and oil using the Peng–Robinson equation of state with the Wong–Sandler mixing rule - Zhong-Lin Yang (KeAi Communications Co., Ltd., 2019)
Abstract This paper presents a three-dimensional, three-phase compositional model considering CO2 phase equilibrium between water and oil. In this model, CO2 is mutually soluble in aqueous and hydrocarbon phases, while other components, except water, exist in hydrocarbon phase. The Peng–Robinson (PR) equation of state and the Wong–Sandler mixing rule with non-random two-liquid parameters are used to calculate CO2 fugacity in the aqueous phase. One-dimensional and three-dimensional CO2 flooding examples show that a significant amount of injected CO2 is dissolved in water. Our simulation shows 7% of injected CO2 can be dissolved in the aqueous phase, which delays oil recovery by 4%. The gas rate predicted by the model is smaller than the conventional model as long as water is undersaturated by CO2, which can be considered as “lost” in the aqueous phase. The model also predicts that the delayed oil can be recovered after the gas breakthrough, indicating that delayed oil is hard to recover in field applications. A three-dimensional example reveals that a highly stratified reservoir causes uneven displacement and serious CO2 breakthrough. If mobility control measures like water alternating gas are undertaken, the solubility effects will be more pronounced than this example.